PENGEMBANGAN MEDIA FLASHCARD BERBASIS KEARIFAN LOKAL SUKU SASAK PADA MATERI BAHASA INDONESIA SISWA KELAS II SDN 11 PRAYA - Erni Yulida; Muhammad Tahir; Vivi Rachmatul Hidayati; Mansur Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the feasibility of flashcard media based on local wisdom of the Sasak tribe, namely songket, as a learning media for Indonesian language for class II. The type of research used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were teachers and students of class II of SDN 11 Praya, while the object was flashcard media based on local wisdom of the Sasak tribe. The instruments used included observation sheets, interviews, expert validation, and teacher and student response questionnaires. The validation results showed that flashcards were declared